The Multiple Dimensions of Space: Spatial Narrative Types and Socio-Cultural Mapping in New Century Chinese Novels - Zhang, Zhiyun (Journal of Ecohumanism, 2024)
This study explores how spatial narratives in new-century Chinese novels reflect and engage with China's rapidly changing socio-cultural landscape. Since the mid-1990s, China's accelerated marketization and globalization have profoundly altered traditional lifestyles and public aesthetics, significantly influencing literary creation. How do contemporary Chinese novelists employ spatial narratives to represent these changes, and what insights do these narratives offer into modern Chinese society? Employing textual analysis grounded in Lefebvre's spatial theory and Soja's Thirdspace concept, this paper examines the manifestations and functions of physical, psychological, and social spaces in new-century Chinese novels. Findings reveal diverse and complex spatial narratives: fragmented physical spaces reflecting globalization's impact, psychological spaces highlighting identity recognition anxiety, and social spaces exposing modern society's alienation and class disparities. This study contributes to a deeper application of spatial narrative theory in Chinese literary research, offering new analytical tools for understanding modern literature and its reflection of social changes. It provides insights into the characteristics and trends of new-century Chinese social culture, promoting further research and theoretical development in related fields.